2021
DOI: 10.1038/s42003-021-02496-1
|View full text |Cite
|
Sign up to set email alerts
|

The development and structure of the mesentery

Abstract: The position of abdominal organs, and mechanisms by which these are centrally connected, are currently described in peritoneal terms. As part of the peritoneal model of abdominal anatomy, there are multiple mesenteries. Recent findings point to an alternative model in which digestive organs are connected to a single mesentery. Given that direct evidence of this is currently lacking, we investigated the development and shape of the entire mesentery. Here we confirm that, within the abdomen, there is one mesente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
0
19
0
2
Order By: Relevance
“…More recently, we built on the work of Heald and Hohenberger and clarified the shape of the mesentery, the anatomical foundation, and fundamental order of the abdomen. 5 During the journey to those discoveries, we again encountered comments that our findings were not new, and in fact were already well known. The story of the mesentery, and its application to colorectal surgery, is thus one of advancements to some and status quo to others.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…More recently, we built on the work of Heald and Hohenberger and clarified the shape of the mesentery, the anatomical foundation, and fundamental order of the abdomen. 5 During the journey to those discoveries, we again encountered comments that our findings were not new, and in fact were already well known. The story of the mesentery, and its application to colorectal surgery, is thus one of advancements to some and status quo to others.…”
mentioning
confidence: 84%
“…We recently found that the mesentery is the organ in and on which all abdominal digestive organs develop and remain directly connected to. 5 As the abdomen develops, it remains composed of two distinct anatomical compartments. The mesenteric compartment or domain includes all abdominal digestive organs positioned on the mesentery.…”
Section: Since 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This erroneous model of mesenteric anatomy gained wide acceptance and was unchallenged for over a century.Recent studies confirm that the mesentery below the duodenojejunal flexure is continuous to the level of the mesorectum. [3][4][5][6][7] Emerging evidence now suggests that continuity of the mesentery also applies above the duodenojejunal flexure and may extend to the level of the oesophagogastric junction. [8][9][10] This differs substantially from conventional descriptions of mesenteric anatomy, which describe the mesentery as discontinuous.Identification of mesenteric continuity has enabled division of the abdomen into two separate compartments.…”
mentioning
confidence: 99%
“…Recent studies confirm that the mesentery below the duodenojejunal flexure is continuous to the level of the mesorectum. [3][4][5][6][7] Emerging evidence now suggests that continuity of the mesentery also applies above the duodenojejunal flexure and may extend to the level of the oesophagogastric junction. [8][9][10] This differs substantially from conventional descriptions of mesenteric anatomy, which describe the mesentery as discontinuous.…”
mentioning
confidence: 99%